Simulated damage of two implant debridement methods: Nonsurgical approach with Teflon and stainless steel hand scalers - João Paulo Mendes Tribst; Amanda Maria de Oliveira Dal Piva; Dimas Renno de Lima; Alexandre Luiz Souto Borges; Marco Antonio Bottino (Wolters Kluwer Medknow Publications, 2018)
Background: Mechanical scaling is the most common treatment of periodontal and peri-implant tissue infections. Aims: This study aimed to evaluate the effect of mechanical prophylactic therapy on the residual stresses in the implant and hand scaler. Settings and Design: For finite-element analysis, an implant-supported prosthesis was created using modeling software with 3 mm of exposed threads. For simulation of a prophylactic mechanical debridement, the active face of the shank was disposed of in contact with the last thread exposed at a 90° angle. Materials and Methods: In the analysis software, the contacts were defined as rough between the instrument and the implant. The cortical bone was fixed and a load of 10 N was applied to the instrument cable. Two simulations were performed according to the instrument material: stainless steel or Teflon. Von-Mises results were obtained. Statistical Analysis Used: No statistical test was used, but, the 500 higher stress peaks in the implant and in the instrument were analyzed for qualitative comparison. Results: Mechanical prophylactic therapy generates higher residual stress on the implant with a stainless steel instrument. There was no difference between the materials for the active tip of the instrument, and the active portion of the shank was the region which concentrated more stress. Conclusions: It is suggested that hand scalers in Teflon are less damaging to the implant, but more susceptible to deformation and possible early failures.